2022
DOI: 10.7717/peerj.12909
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals the potential biological function of FSCN1 in HeLa cervical cancer cells

Abstract: Fascin actin-bundling protein 1 (FSCN1), an actin-bundling protein associated with cell migration and invasion, is highly expressed in various tumor tissues. FSCN1 has also been reported to be a marker of increased invasive potential in cervical cancers. However, the functions of FSCN1 are still not fully understood in cervical cancers. Here, the gene expression profile of HeLa cells transfected with FSCN1 shRNA (shFSCN1) was compared with that of cells transfected with empty vector (shCtrl). The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…m6A methyltransferase METTL14 can catalyse m6A methylation modification on mRNA, while reading protein IGF2BP3 can recognize the modification and affect gene expression, thereby affecting gene expression. FSCN1 is closely related to cell motility, EMT, migration, inflammation and immunity and has been reported as a potential therapeutic target for various cancers 20–23 . Interestingly, FSCN1 was predicted to have multiple m6A modification sites on its mRNA sequence through a sequence‐based m6A modification site predictor (http://www.cuilab.cn/sramp/).…”
Section: Resultsmentioning
confidence: 99%
“…m6A methyltransferase METTL14 can catalyse m6A methylation modification on mRNA, while reading protein IGF2BP3 can recognize the modification and affect gene expression, thereby affecting gene expression. FSCN1 is closely related to cell motility, EMT, migration, inflammation and immunity and has been reported as a potential therapeutic target for various cancers 20–23 . Interestingly, FSCN1 was predicted to have multiple m6A modification sites on its mRNA sequence through a sequence‐based m6A modification site predictor (http://www.cuilab.cn/sramp/).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, several studies have been conducted on the potential mechanisms through which FSCN1 affects the expression of a large number of genes ( 29 , 31 ). For example, Saad et al ( 31 ) revealed that phosphorylated FSCN1 (p-FSCN1) localized in the nucleus and regulated histone methylation and gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…22 Guo and his colleagues demonstrated that FSCN1 could be an indicator of enhanced invasive effect in CC for its positive correlation with a proangiogenic factor ANGPTL4, as revealed by the expression analysis of CC tumor tissue in TCGA. 23 The oncogenic role of Cadherin-3 (CDH3) has been well documented. In breast cancer, CDH3 overexpression mediates aggressive behavior of tumor cells, mainly associating with the exaggerated stem cell properties.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the fascin family, FSCN1 is upregulated in various tumor tissues, including CC 22 . Guo and his colleagues demonstrated that FSCN1 could be an indicator of enhanced invasive effect in CC for its positive correlation with a proangiogenic factor ANGPTL4, as revealed by the expression analysis of CC tumor tissue in TCGA 23 . The oncogenic role of Cadherin‐3 (CDH3) has been well documented.…”
Section: Discussionmentioning
confidence: 99%